Storie di vita e di malavita. Criminali, poveri e altri miserabili nelle carceri di Milano alla fine del medioevo - Gazzini, Marina (Reti Medievali E-Book, 2017)
The volume deals with an uncommon theme in medieval history: the prison and its inhabitants. In the medieval prison, the prisoners - waiting for their sentence, or imprisoned for debts, or because socially dangerous or found guilty of a crime - were not abandoned to themselves; families, the Church, devout lay people and public authorities took charge of their needs. In the case of Milan, the prison system and the relationship between prisoners, justice and mercy takes on particular nuances. Prisons (including private ones) are numerous and scattered throughout the city: the largest is a prison-hospital, which certainly imprisons, but suggests that it is useful (for economic reasons) to help the survival of the offender and their return to society. The citizens of Milan in the 15th Century are also aware of the risks of abandoning prisoners (men and women) to a justice that, for its costs, only protects the strongest. Here are the Protectors of prisoners: useful not only to the weak ones in prison, but also to the Dominus, who supports them. The duke, interested in correcting the system excesses, is also (and perhaps above all) eager to show himself merciful, and as such superior to the law. Investigating the condition of prisoners thus proves to be a way to grasp not only the dynamics of social exclusion and inclusion relevant to the control of deviance, but also the mechanisms of relationship between rulers and subjects in the late Middle Ages.